Percepções de pais e mães a respeito do comportamento de seus filhos gêmeos - Bochernitsan, Elisa (2012)
The present Master s Degree thesis consists of two studies in accordance with the rules of the Graduate Program in Psychology of the Pontifical Catholic University of Rio Grande do Sul (PUCRS). The first study is a literature review entitled Psychological and Social Aspects of Multiple Birth , aimed at researching articles published on twins and analyzed with the aid of the Child Behavior Checklist (CBCL). Researchers examined the goals, the data collection process, as well as the conclusions and contributions of each article found, in addition to relevant and different aspects of the research over time. In order to collect articles on twins that were analyzed with the support of the CBCL tool, researchers explored the following databases: PubMed, Bvs-Psi, PsycINFO, and Web of Science. Articles related to psychopathology or the issue of heredity/genetics versus the environment were excluded. There is very little literature that addresses the perception of mothers and fathers in relation to twins behavior with the use of the CBCL tool in international articles, and there is nothing in Brazilian articles. The second study, Twins: Perceptions of Mothers and Fathers , aimed at:a)Verifying the difference in the perception of mothers and fathers in relation to twins behavior, concerning the group of twins indicated by mothers and fathers as physically similar or different; b)Verifying the difference in the perception of mothers and fathers in relation to their twins behavior; c)Verifying the difference in the perception of mothers and fathers in relation to their twins behavior, whether boys or girls; d)Examining the perception of mothers and fathers concerning the behavior of a twin in relation to another. Results show twins perceived by mothers and fathers as being physically similar do not demonstrate significant difference in relation to those perceived as physically different. Researchers also found that between them mothers and fathers distinguish their twins behavior, that is: they perceive the twins differently. There were no significant differences in the perception of mothers and fathers when their twins were boys or girls. Data also showed that there is a correlation from regular to strong in the perception of the twins' behavior towards each other by mothers and fathers, at all levels. These findings are discussed based on the international literature reviewed. New studies are important so that people can find out more about the way mothers and fathers view their twins behavior.